Review of range-based positioning algorithms - Yan, J.; Tiberius, C.C.J.M.; Janssen, G.J.M.; Teunissen, Peter; Bellusci, G. (Institute of Electrical and Electronics Engineers, 2013)
This tutorial reviews algorithms which turn measured ranges into position solutions. From their basic mathematical principles, we relate and compare relevant aspects of these algorithms. Special attention is given to the direct (non-iterative) algorithms, which are frequently applied in indoor positioning. Most of them are shown to be essentially the same, as they can be related through applying different weighting schemes. This tutorial is intended as a useful guide to help researchers and system designers evaluate and select appropriate range-based positioning algorithms for their applications at hand.